Palaeoenvironmental and palaeoclimatic reconstruction of the Latest Pleistocene of El Portalón Site, Sierra de Atapuerca, northwestern Spain - López García, Juan Manuel; Blain, Hugues Alexandre; Cuenca Bescós, Gloria; Ruiz Zapata, María Blanca; Dorado Valiño, Miriam; Gil García, María José; Valdeolmillos, Ana; Ortega, Ana Isabel; Carretero, José Miguel; Arsuaga, Juan Luis; Bermúdez de Castro, Jose María; Carbonell, Eudald (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
The site of El Portalón is the entrance to the Cueva Mayor karst system, located in the Sierra de Atapuerca (Burgos, Spain). This is an important Holocene archaeological site,which was excavated in the 1970s but from which little has been published. New excavations starting in 2000 have highlighted a deep stratigraphical sequence, with human occupations starting at the end of the Late Pleistocene. In this paper, we present for the first time, on the basis of the small-vertebrate assemblage, palaeoenvironmental and palaeoclimatic reconstructions of the Latest Pleistocene of the Sierra de Atapuerca, well known for its Early to Middle Pleistocene human-bearing localities. The small vertebrates of El Portalón comprise at least 25 species: 4 amphibians (Alytes obstetricans, Bufo bufo, Bufo calamita and Rana temporaria); 3 squamates (an indeterminate small-size lacertid, an indeterminate large colubrine and Vipera sp.); 6 insectivores (Sorex gr. coronatus-araneus, Sorex minutus, Neomys fodiens, Neomys anomalus, Talpa europaea and Galemys pyrenaicus); 2 bats (Myotismyotis and Myotis gr. myotis-blythi); 10 rodents (Microtus arvalis, Microtus agrestis, Microtus oeconomus, Iberomys cabrerae, Chionomys nivalis, Terricola duodecimcostatus, Arvicola sapidus, Arvicola terrestris, Apodemus sylvaticus and Eliomys quercinus). These taxa, many of which are ecothermal (sensitive to temperature) show variations in their taxonomic diversity throughout the sequence. Although, with the exception of M. oeconomus, they do not differ fromthe extant fauna of the Iberian Peninsula, they do so in the abundance of their taxonomic assemblage. When the small vertebrates are grouped and studied in terms of vertical trends through the sequence, it is possible to follow environmental and climatic changes. Results from the small-vertebrate associations indicate that the landscape had open habitats in the vicinity of the Atapuerca caves throughout the sequence,withwet locales in the surrounding area. Woodland and water stream meadows were more ...